The impact of emotional profile on learning: the case of public elementary school learner - Bouchra KHAZRAJ; Nadia SAQRI (African Scientific Journal, 2023)
The learner experiences many emotions: getting ready at home, on the way to school, in front of the portal, in the playground and in the classroom. These emotions need to be diagnosed, assessed and taken into consideration for the purpose of creating an atmosphere conducive to learning. Teachers need to be aware of their learners’ emotional state in order to be in tune with them (knowing how to deal with emotionally sensitive cases, devising appropriate teaching strategies, etc.) The present work highlights the emotional state of the child during the three primary cycles following an analysis of certain cases in Moroccan public schools. We are going to look at these emotions from the point of view of the teacher and the protagonist (the learner), with the aim of developing coaching approaches that teachers can adopt to help their students intelligently manage their emotions, strengthen their emotional identity and consequently enhance their learning